Nontraditional security challenges in Southeast Asia the transnational dimension - Freedman, Amy L.; Murphy, Ann Marie (Boulder, Colorado Lynne Rienner Publishers, Inc., 2018)
"Explores the factors that continue to impede cooperation in combating nontraditional, transnational security threats in Southeast Asia"--Provided by publisher.
Nontraditional security threats in Southeast Asia : the transnational dimension -- Climate change : complex patterns of conflict and cooperation -- Food security : beggar thy neighbor? -- Water security : droughts, deluges, and dams -- Health security : avian influenza and disease protocols -- Migration : divergent interests of sending and receiving states -- Looking forward : prospects for cooperation and conflict.
Includes bibliographical references and index.
Keywords: Security, International -- International cooperation. -- Southeast Asia; National security -- International cooperation. -- Southeast Asia; Emergency management -- International cooperation. -- Southeast Asia